2017
DOI: 10.1038/cdd.2016.155
|View full text |Cite
|
Sign up to set email alerts
|

The BCL-2 pro-survival protein A1 is dispensable for T cell homeostasis on viral infection

Abstract: The physiological role of the pro-survival BCL-2 family member A1 has been debated for a long time. Strong mRNA induction in T cells on T cell receptor (TCR)-engagement suggested a major role of A1 in the survival of activated T cells. However, the investigation of the physiological roles of A1 was complicated by the quadruplication of the A1 gene locus in mice, making A1 gene targeting very difficult. Here, we used the recently generated A1−/− mouse model to examine the role of A1 in T cell immunity. We confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 50 publications
0
35
0
1
Order By: Relevance
“…The in vivo T cell stimulation has been examined using models of influenza and chronic LCMV infection, but no abnormalities were seen in A1 −/− mice. 44 Furthermore, upon immunisation with NP-KLH, A1 −/− mice failed to reveal any B cell activation defects in vivo. 44 It has been reported that in mice lacking the A1-a isoform, the inflammatory response to infection with Toxoplasma gondii was less severe compared with wild-type controls in terms of overall peritoneal leukocyte cellularity, but the proportions of granulocytes recruited to the peritoneal cavity were comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo T cell stimulation has been examined using models of influenza and chronic LCMV infection, but no abnormalities were seen in A1 −/− mice. 44 Furthermore, upon immunisation with NP-KLH, A1 −/− mice failed to reveal any B cell activation defects in vivo. 44 It has been reported that in mice lacking the A1-a isoform, the inflammatory response to infection with Toxoplasma gondii was less severe compared with wild-type controls in terms of overall peritoneal leukocyte cellularity, but the proportions of granulocytes recruited to the peritoneal cavity were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…44 Furthermore, upon immunisation with NP-KLH, A1 −/− mice failed to reveal any B cell activation defects in vivo. 44 It has been reported that in mice lacking the A1-a isoform, the inflammatory response to infection with Toxoplasma gondii was less severe compared with wild-type controls in terms of overall peritoneal leukocyte cellularity, but the proportions of granulocytes recruited to the peritoneal cavity were comparable. 45 This suggests that loss of A1 may impair the survival of certain cell types of the immune system to a minor extent, but not enough to preclude A1-deficient mice to respond adequately to infectious challenges.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work examining a complete A1 KO mouse showed no decrease in the overall numbers of naïve T cells (225). In activated T cells, A1 is mainly thought to be critical for activated T cell survival due to its rapid response to TCR signaling and the fact that it does not inhibit T cell proliferation (208, 209).…”
Section: Bcl-2 Family Membersmentioning
confidence: 99%
“…Preliminary data from our lab shows higher A1 expression in CD4 effector cells compared to CD8 effectors at the peak of an anti-viral response, suggesting a CD4-specific role for A1 in effector T cell survival. Although the recent work in the complete A1 KO suggested that effector T cell responses were normal, it should be noted that this work did not examine the CD4 + T cell response using MHC tetramers, but instead just looked at overall numbers of memory cells after infection (225). In addition, the mice did display a significant loss of memory CD4 + T cells, suggesting that either the contraction of the effector response or the maintenance of the memory CD4 compartment relies substantially on A1.…”
Section: Bcl-2 Family Membersmentioning
confidence: 99%
“…In mice, A1 is produced by three independent genes (Bcl2a1-a, Bcl2a1-b and Bcl2a1-d) [5] and is mainly expressed in the haematopoietic system where it is dynamically regulated in response to antigens or inflammatory cues engaging NF-kB [6], NF-AT [7], and PU.1 [8] transcription factors. Mice that lack all functional Bcl2a1 genes do not exhibit major impairments in the development and composition of their immune system [9] or T cell-mediated immune responses [10]. The human homologue, BFL1, which is highly homologous to A1 (72% amino acid identity) is encoded by a single gene [11].…”
Section: Introductionmentioning
confidence: 99%